hnRNPU-mediated pathogenic alternative splicing drives gastric cancer progression - Guoguo Jin; Yanming Song; Shaobo Fang; Mingyang Yan; Zhaojie Yang; Yang Shao; Kexin Zhao; Meng Liu; Zhenwei Wang; Zhiping Guo; Zigang Dong (Journal of Experimental & Clinical Cancer Research)
Abstract Background Alternative splicing (AS) is a process that facilitates the differential inclusion of exonic sequences from precursor messenger RNAs, significantly enhancing the diversity of the transcriptome and proteome. In cancer, pathogenic AS events are closely related to cancer progression. This study aims to investigate the role and regulatory mechanisms of AS in gastric cancer (GC). Methods We analyzed AS events in various tumor samples and identified hnRNPU as a key splicing factor in GC. The effects of hnRNPU on cancer progression were assessed through in vitro and in vivo experiments. Gene knockout models and the FTO inhibitor (meclofenamic acid) were used to validate the interaction between hnRNPU and FTO and their impact on AS. Results We found that hnRNPU serves as a key splicing factor in GC, and its high expression is associated with poor clinical prognosis. Genetic depletion of hnRNPU significantly reduced GC progression. Mechanistically, the m6A demethylase FTO interacts with hnRNPU transcripts, decreasing the m6A modification levels of hnRNPU, which leads to exon 14 skipping of the MET gene, thereby promoting GC progression. The FTO inhibitor meclofenamic acid effectively inhibited GC cell growth both in vitro and in vivo. Conclusion The FTO/hnRNPU axis induces aberrant exon skipping of MET, thereby promoting GC cell growth. Targeting the FTO/hnRNPU axis may interfere with abnormal AS events and provide a potential diagnostic and therapeutic strategy for GC. Graphical Abstract Schematic model for the findings of this work: Aberrant hnRNPU in GC binds FTO. The m6A-modified hnRNPU transcripts are recognized by m6A reader YTHDF3 and subsequently demethylated by FTO. This demethylation enhances the stability of hnRNPU mRNA, consequently promoting alternative splicing of MET. The altered splicing pattern ultimately contributes to the proliferation of GC cells.